Bahasa Inggris sebagai Daya Tarik Pemasaran: Studi Pengaruhnya terhadap Minat Konsumen Yotta di Makassar - Megawati, Megawati; Mustaqim, Afifah Maghfirah; Lukman, Lukman (JURNAL PENA, 2025)
In the era of globalization and digitalization, use English in marketing is increasingly becoming a common strategy, even among local business actors. This study aims to analyze the effect of the use of English in menu naming on consumer interest in the Yotta culinary brand in Makassar City. This study uses a literature study approach by analyzing various scientific journals from the last 10 years that are relevant to the topics of marketing, consumer behavior, and the use of foreign languages in branding strategies. The results of the study indicate that English not only functions as a means of communication, but also as a symbol of modernity, exclusivity, and visual appeal that can increase consumers' positive perceptions of a product. On the other hand, the use of foreign languages also has challenges, especially if it does not consider the diverse backgrounds of local consumers. Therefore, a bilingual strategy or additional explanation is considered a more inclusive approach. This study provides important implications for MSMEs and local brands in designing effective, adaptive, and relevant communication strategies for market segments. These findings also encourage further research on aspects of linguistic integration in marketing communications, especially in the context of local culture in Indonesia. Keywords: english, marketing, consumer interest, yotta, branding.